2013
DOI: 10.1021/ie4002603
|View full text |Cite
|
Sign up to set email alerts
|

Castor Oil Based Hyperbranched Poly(ester amide)/Polyaniline Nanofiber Nanocomposites as Antistatic Materials

Abstract: Biobased hyperbranched poly(ester amide) (HBPEA)/polyaniline (PAni) nanofiber nanocomposites were prepared by incorporating the as-synthesized PAni nanofiber at varied weight percentages by an ex situ polymerization technique. Fourier transform infrared spectroscopic analyses indicated the interactions of the benzenoid–quinoid moieties of PAni with HBPEA. The transition from liquidlike to solidlike behavior of the nanocomposites with a percolation threshold at 10 wt % nanofiber content was studied using dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The shear viscosity of them decreased with increasing shear rate showing shear-thinning behavior signifying the formation of threedimensional network structure. 21,37 The shear viscosity also increased drastically with the content of CD over a broad range of shear rates due to the above reasons.…”
Section: Rheological Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The shear viscosity of them decreased with increasing shear rate showing shear-thinning behavior signifying the formation of threedimensional network structure. 21,37 The shear viscosity also increased drastically with the content of CD over a broad range of shear rates due to the above reasons.…”
Section: Rheological Studymentioning
confidence: 97%
“…The viscous and elastic characters of the pristine polyester and nanocomposites before curing are characterized by loss modulus (G″) and storage modulus (G′) respectively. 37,38 The viscoelastic properties of the pristine polyester and nanocomposites were examined by the frequency sweep experiment. G′ and G″ were measured as a function of frequency (1 to 10 s −1 ) under constant temperature (25 °C) and constant stress (20 Pa).…”
Section: Rheological Studymentioning
confidence: 99%
“…It is known that polymer with (τ 1/2 ) lower than 10 s are considered as antistatic materials, what is more, the shorter the half‐life decay time is, the better the antistatic property will be . These results also indicated that PANI‐ g ‐SWPU coatings can endow the paper with enhanced antistaticity, the as‐prepared coated paper is able to be utilized in the antistatic material field …”
Section: Surface Resistivity Of Pani‐g‐swpu Filmsmentioning
confidence: 86%
“…Then castor oil, was added and the mixture was refluxed for 30 minutes at 150 °C . Diethanolamine was added with 10 mol% excess to the methylester formed and refluxed for one and a half hour with continuous stirring under N 2 gas atmosphere [20]. Thus, the synthesis described is however beyond the purpose of our study.…”
Section: Literature Reviewmentioning
confidence: 99%